The Importance of Guidance and Motivational Encouragement: The Significance of Leadership and Communication in Organizational Management - Djoko Soelistya; Rahmat Agus Santoso; Akhsin Akhsin; Triasmono Triasmono (Kontribusia : Research Dissemination for Community Development, 2023)
One effort to produce quality students is to increase teacher motivation and communication skills. School leaders need to pay attention to teacher motivation in dealing with difficult situations in order to improve the quality of education. In this assumption, motivation and communication are considered to be able to improve teacher performance and achieve educational goals. In addition to the teacher's communication role, the principal's leadership style also has an important influence. If motivation and communication are not optimal, this can have a negative impact on teacher performance. This phenomenon has the potential to result in a decrease in teacher performance.The purpose of this community service (PKM) view is that the success of schools in improving teacher performance can be influenced by the training and counseling provided to teachers, with the aim of improving the quality of teacher resources. One effort that can be done is to provide motivation and teach how to communicate well between teachers and students in overcoming obstacles in the teaching process and dealing with teaching-learning situations. The principal's concern through respect for teacher performance also plays a role in this, with the leadership style shown by the principal.Motivational counseling, attended by teachers and school principals, yielded results (1) Community Service Activities (PKM) can provide enthusiasm for changing maximum performance in school governance; (2) Community Service Activities (PKM) can improve and change communication between teachers and parents of students to become more humane and create mutual trust and respect; (3) Community Service Activities (PKM) can provide changes and evaluations of the Principal's leadership style and touch on improving teacher performance, building trust in teachers for the potential of teacher resources.Hope for teachers and school principals in PKM activities to provide changes and improve teacher performance and integrated communication between teachers, school principals and student guardians, so as to have an increased performance impact to assist in governance at the GKB Gresik Muhammadiyah 1 Elementary School Foundation